English: INDIKATOR KINERJA ENERGI BANGUNAN PELAYANAN KESEHATAN: STUDI KASUS RUMAH SAKIT KECIL DI INDONESIA - Simarmata, Todo H (Jurnal Nasional Pengelolaan Energi MigasZoom, 2023)
Energy is needed to guarantee the reliable and safe operation of healthcare buildings. The hospitals and other healthcare building energy performance have been investigated using several sets of energy performance indicators (EnPIs) formulation in several contexts. Often, those EnPIs are meaningless compared to other healthcare buildings, or they are restricted in their ability to guide energy investment planning or operation. This study examined four approaches—kWh/sqm/year, kWh/bed-day, kWh/overnight inpatient, and kWh/sum of inpatient and outpatient—for calculating EnPIs of a small-sized government hospital. The analysis focused on methods for defining EnPIs in the healthcare industry. With a value of 4.62 kWh/patient, it was found that the kWh/sum of in and outpatient was the optimal EnPI model.